2023
DOI: 10.1111/bjh.18884
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate dehydrogenase 1: A novel metabolic target in inhibiting acute myeloid leukaemia progression

Abstract: Summary Glutamine metabolic reprogramming in acute myeloid leukaemia (AML) cells contributes to the decreased sensitivity to antileukemic drugs. Leukaemic cells, but not their myeloid counterparts, largely depend on glutamine. Glutamate dehydrogenase 1 (GDH1) is a regulation enzyme in glutaminolysis. However, its role in AML remains unknown. Here, we reported that GDH1 was highly expressed in AML: high GDH1 was one of the independent negative prognostic factors in AML cohort. The dependence of leukaemic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Metabolomics studies have revealed that AML cells exhibit an increased demand for glucose and glutamine, channeling these resources to sustain proliferation advantages compared to normal cells [ 49 , 50 ]. Addiction to glucose produces more α-ketoglutaric acid (α-KG), an intermediate product of the mitochondrial tricarboxylic acid cycle, converted to glutamate by aminotransferase [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics studies have revealed that AML cells exhibit an increased demand for glucose and glutamine, channeling these resources to sustain proliferation advantages compared to normal cells [ 49 , 50 ]. Addiction to glucose produces more α-ketoglutaric acid (α-KG), an intermediate product of the mitochondrial tricarboxylic acid cycle, converted to glutamate by aminotransferase [ 51 ].…”
Section: Discussionmentioning
confidence: 99%